Development of learning model problem investigation discussion sharing to improve science literacy and collaboration - Dian Nur Indah Sari; S. Suratno; Pramudya Dwi Aristya Putra (Universitas Muhammadiyah Malang, 2024)
Science literacy and collaboration skills in schools are still very low and the learning models applied by teachers still have shortcomings that need to be improved. Based on this, researchers are interested in developing a learning model called Problem Investigation Discussion Sharing (PIDS), which combines three learning models: Problem Based Learning (PBL), Inquiry Learning, and Discovery Learning. The purpose of this study is to test the validity, practicality and effectiveness of the PIDS learning model. This study uses the ADDIE design with the phases Analyze, Design, Development, implementation, and evaluation. The research was conducted in three schools with three validators. Validation results obtained a score of 89% in valid categories. Practicality results of 86% in highly practical categories; N-gain results in science literature of 0.65 in medium categories and collaboration results of 78.3% in collaborative categories. In conclusion, the PIDS learning model is valid, practical and effective.